2018
DOI: 10.1007/s10265-018-1031-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of asymmetric polar auxin transport by PsPIN1 in endodermal tissues of etiolated Pisum sativum epicotyls: focus on immunohistochemical analyses

Abstract: This manuscript reports the production of specific polyclonal antibodies for PsPIN1, a putative auxin efflux carrier in Alaska pea (Pisum sativum L.) plants, and the cellular immunolocalization of PsPIN1. When pea seeds were set with the seed axis horizontal to the upper surface of a rockwool block, and allowed to germinate and grow for 3 days in the dark, the epicotyl grew upward. On the other hand, the application of 2,3,5-triiodobenzoic acid (TIBA) inhibited graviresponse. In the subapical epicotyl regions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The phytohormone auxin, indole 3-acetic acid (IAA), plays a crucial role in plant growth and development, including embryogenesis ( Friml et al, 2003 ; Blilou et al, 2005 ; Morris et al, 2005 ; Leyser, 2017 ), organogenesis ( Benkova et al, 2003 ; Reinhardt et al, 2003 ; Heisler et al, 2005 ; Smekalova et al, 2014 ; Contreras-Cornejo et al, 2015 ; Enders et al, 2017 ; Wójcikowska and Gaj, 2017 ; Corredoira et al, 2017 ; Zhao, 2018 ), tissue patterning, tropism and growth responses to environmental stimuli ( Benkova et al, 2003 ; Leyser, 2003 ; Reinhardt et al, 2003 ; Morris et al, 2004 ; Simonini et al, 2016 ; Liu et al, 2017 ; Kamada et al, 2018 ). The involvement of auxin in this multiplicity of biological processes results from its regulation of cell division, expansion and differentiation ( Chen and Baluska, 2013 ).…”
Section: Mapk Modules Involed In Auxin Signalingmentioning
confidence: 99%
“…The phytohormone auxin, indole 3-acetic acid (IAA), plays a crucial role in plant growth and development, including embryogenesis ( Friml et al, 2003 ; Blilou et al, 2005 ; Morris et al, 2005 ; Leyser, 2017 ), organogenesis ( Benkova et al, 2003 ; Reinhardt et al, 2003 ; Heisler et al, 2005 ; Smekalova et al, 2014 ; Contreras-Cornejo et al, 2015 ; Enders et al, 2017 ; Wójcikowska and Gaj, 2017 ; Corredoira et al, 2017 ; Zhao, 2018 ), tissue patterning, tropism and growth responses to environmental stimuli ( Benkova et al, 2003 ; Leyser, 2003 ; Reinhardt et al, 2003 ; Morris et al, 2004 ; Simonini et al, 2016 ; Liu et al, 2017 ; Kamada et al, 2018 ). The involvement of auxin in this multiplicity of biological processes results from its regulation of cell division, expansion and differentiation ( Chen and Baluska, 2013 ).…”
Section: Mapk Modules Involed In Auxin Signalingmentioning
confidence: 99%
“…Phylogenetic relationships revealed that PsPIN1 belongs to the same clade as AtPIN1, and PsPIN2 and PsPIN3 belong to the same subclade including AtPIN3, AtPIN4, and AtPIN7 [39]. Immuno-histochemical analysis using specific polyclonal antibodies for PsPIN1 demonstrated the localization of PsPIN1 in the basal side of the plasma membrane of cells in endodermal tissues in etiolated pea seedlings [48], suggesting that PsPIN1 plays a fundamentally important role in directional transport of auxin as does AtPIN1. These results suggest a possible involvement of reduced levels of PsAUX1 and PsPIN1 carrier proteins in auxin influx and efflux, respectively, via a reduction of expression of both PsAUX1 and PsPIN1 mRNA, in the reduction of polar auxin transport by DHCL in etiolated pea epicotyls.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, polar auxin transport regulated by PsAUX1 and PsPIN1 carrier proteins of auxin might be highly regulated by the level of mRNA accumulation affected by endogenous IAA. NPA inhibits IAA transport by specific binding to a so-called NPA receptor, thereby blocking the carrier-mediated efflux of IAA [48], whereas IAA does not compete with NPA for the binding site [9]. Morphactin has been shown to bind to the NPA receptor, suggesting that it acts by the same mechanism as NPA [50].…”
Section: Discussionmentioning
confidence: 99%
“…Hormones, like auxin, abscisic acid (ABA), jasmonic acid (JA), salicylic acid (SA), ethylene (ET), brassinosteroids (BR) and gibberellins (GA), can differentially select distinct MAPK module structures (or cascade) that subsequently trigger a required biological process [20,21,24,42,43,[45][46][47][48][49][50][51]. MAPK normally exchanges signalling with auxin.…”
Section: Mapk-core Analysismentioning
confidence: 99%